The Role and Implications of Houthis Action in Israel-Hamas War 2023-2024 - Agubamah , Edgar (Kashere Journal of Politics and International Relations, 2025)
The Israel-Hamas war has lingered for years been part of the larger Israel-Palestinian conflict. The claim to land and sovereignty has been at the core of this altercation between Israel and Hamas. As earlier said the crisis has been long in origin but that of October 7th, 2023 assumed a dangerous and wider dimension of global proportion. This particular crisis has drawn the attention of many state and non-state actors of which the Houthis in Yemen is one of them. The actions of these state and non-state actors have complicated, exacerbated, and escalated this war. This is why this work focus on the role and implications of Houthis in this Israel-Hamas imbroglio. In line with this some pertinent questions were raised. Who are the Houthis? What made the Houthis to engage in this precarious war? What is their role in the war? What are the implications of their role? In order to find answers to these questions documentary evidence was used to gather data for the work from books, journals, magazines, Newspapers and internet materials. The ideological theory was used as an analytical tool. From these gatherings and analysis, the work discovered that the Houthis are a group of people from Yemen fighting to end political and economic marginalization within their country and with hatred against the Saudis, UAE, US and Israel as depicted by their slogan.